Plastic bag ban in the context of Corporate Social Responsibility: consumption and trade vis-a’-vis environmental sustainability concerns - Zen, Irina Safitri (Springer Nature, 2020)
A corporate social responsibility (CSR) initiative by supermarkets have made significant contributions to the elimination of plastic bags consumption, hence establishing a new norm in the society. This means that the various initiatives conducted in promoting a sustainable shopping lifestyle have challenged the ‘status quo’ of providing free single-use plastic bags for consumers’ convenience. Moreover, pressure from global environmental challenges for plastic pollution and the multifaceted global trade environment has made an impact on the corporate sector. This paper analyses the multifaceted involvement of the CSR initiatives of supermarkets in a global movement on the anti-plastic bag ban by examining Malaysia’s No Plastic Bag Campaign (NPBC) as a case study. Previous studies have deployed the qualitative framework analysis and adopted the Caroll’s global CSR pyramid framework to defragment the complexities of the supermarkets’ CSR initiatives. Based on the content analysis, which is reinforced by the descriptive analysis of the consumer’s survey, the result revealed several competitive advantages of the corporate sector’s involvement in anti-plastic bag initiatives. These advantages include elaborating on the concept of supermarket CSR in the context of the plastic bag ban, detangling the multifaceted discussion around supermarket CSR and clarifying the crucial role of supermarket CSR in the governance overall involved in the plastic bag ban from the business sector’s perspective. Finally, by deploying the global CSR pyramid framework, the study outlined the CSR initiatives of supermarkets in terms of the anti-plastic bag campaign from four key responsibilities; economic, ethical, legislative and philanthropy. The study revealed several strategic competitive advantages. Hence, the involvement of the CSR supermarket initiative’s contribution to a global movement of anti-plastic bag ban is crucial.